Systematics of a species complex in the deep-sea genus Eurycope, with a revision of six previously described species (Crustacea - Wilson, G. D. F. (Isopoda, Eurycopidae). Bulletin of the Scripps Institution of Oceanography, 1982)
The genus Eurycope contains a taxonomically difficult species complex limited to the deep North Atlantic Ocean. The complex consists of 12 species, some of which have been hidden in the literature under the name of one of its members, Eurycope complanata Bonnier. This paper develops methods for identifying these species, 10 of which are new, and presents descriptions and a key. In addition, another closely related species group found only in the Norwegian and Arctic seas is redescribed and included in the key. The phylogenetic relationships of the complanata complex are explored and the results are displayed in a cladogram. The complex consists of two main groups with one intermediate species. Within one of the groups, there are two pairs of sibling species along with several species that have ambiguous relationships. Geographically co-occurring species pairs are examined. Each pair has mutually different morphologies of taxonomically important characters, size andlor mandibular shape, and it is suggested that resource partitioning between these pairs may occur.
World Isopoda DB